Drip Irrigation of Tomatoes in Biskra: Water Saving and Economic Profitability - Kamel Djaghrouri; Mohammed Faci; Hacène Cherif (Annals of Arid Zone, 2024)
A field survey of thirty tomato growing greenhouses in Biskara region of Algeria was undertaken to find out the kind of the irrigation method being used and to assess their water productivity and economics. 30% of the greenhouses employed drip irrigation (9 farms), 20% (6 farms) utilized furrow irrigation, while the rest used the mixed irrigation. The sowing/transplantation of tomato in greenhouses in the region was carried out from August to October. The production started from March and ended in June. The selling price per kilogram of tomatoes ranged between 25 and 105 Algerian Dinar (DA). Results revealed that greenhouses using drip irrigation had higher water productivity and lower total water requirements. Greenhouses using drip irrigation produced 71.7 tons tomatoes ha-1, which is 33.7% higher than that using furrow irrigation. Drip irrigated greenhouses exhibited maximum water productivity of 20.4 kg m3. Total water consumption in the greenhouses using drip was 3722.2 m3 ha-1 while it was 10248 m3 ha-1 in the furrow irrigated. Average financial returns from the drip irrigated greenhouses were about 36% higher than farms using furrow irrigation.